2018
DOI: 10.1186/s12859-018-2388-7
|View full text |Cite
|
Sign up to set email alerts
|

Computational prediction of inter-species relationships through omics data analysis and machine learning

Abstract: BackgroundAntibiotic resistance and its rapid dissemination around the world threaten the efficacy of currently-used medical treatments and call for novel, innovative approaches to manage multi-drug resistant infections. Phage therapy, i.e., the use of viruses (phages) to specifically infect and kill bacteria during their life cycle, is one of the most promising alternatives to antibiotics. It is based on the correct matching between a target pathogenic bacteria and the therapeutic phage. Nevertheless, correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 39 publications
1
49
0
Order By: Relevance
“…It was seen previously that SVM sometimes fails when it is intended for distinguishing fine biomedical properties such as disease progression prognosis or assessment of clinical efficiency of drugs for an individual patient, using high throughput molecular data, e.g., complete DNA mutation or gene expression profiles (Ray and Zhang, 2009; Babaoglu et al, 2010). Particularly, for many biologically relevant applications, SVM occurred either fully incapable to predict drug sensitivity (Turki and Wei, 2016), or demonstrated poorer performance than competing method for machine learning (Davoudi et al, 2017; Cho et al, 2018; Jeong et al, 2018; Leite et al, 2018; Sauer et al, 2018; Yosipof et al, 2018). Thus, the tool for improvement of SVM performance is certainly needed.…”
Section: Discussionmentioning
confidence: 99%
“…It was seen previously that SVM sometimes fails when it is intended for distinguishing fine biomedical properties such as disease progression prognosis or assessment of clinical efficiency of drugs for an individual patient, using high throughput molecular data, e.g., complete DNA mutation or gene expression profiles (Ray and Zhang, 2009; Babaoglu et al, 2010). Particularly, for many biologically relevant applications, SVM occurred either fully incapable to predict drug sensitivity (Turki and Wei, 2016), or demonstrated poorer performance than competing method for machine learning (Davoudi et al, 2017; Cho et al, 2018; Jeong et al, 2018; Leite et al, 2018; Sauer et al, 2018; Yosipof et al, 2018). Thus, the tool for improvement of SVM performance is certainly needed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is used for the prediction of various chemical and biological properties from chemical structures (e.g. [5][6][7]). Classical multivariate statistics and machine learning approaches include logistic regression, support vector machines, decision trees and Bayesian networks.…”
Section: Introductionmentioning
confidence: 99%
“…The use of phages could also enable to combat current unculturable bacteria, on the condition that they can easily be identified through genomic approach. It has been suggested that machine learning approaches can be utilized to either identify, or generate through synthetic genomics, based on the genomic information provided on the bacterial target ( Leite et al, 2018 ; Martorell-Marugán et al, 2019 ; Baláž et al, 2020 ; Pirnay, 2020 ).…”
Section: Discussionmentioning
confidence: 99%